Tide and tempest : a novel - Ludwig, Elizabeth (Ludwig, Elizabeth. Edge of freedom, 2014)
"In the riveting conclusion to the EDGE OF FREEDOM series, Captain Keondric Morgan believes Tillie's husband was murdered two years ago when he died crossing to America. Now can Keondric save Tillie from the same fate?"--